Development of Blended Learning-Based Mathematics Learning Devices Viewed from The Learning Styles of Students at SMP Muhammadiyah 2 Mariyai, Sorong District - SIDDIK, MUSTAFAH; HASANAH, MUARIEF (Journal of Scientific Research, Education, and Technology (JSRET), 2023)
Learning mathematics at school still has low learning outcomes. There are students who have different learning styles who catch learning faster by using an auditory style or prefer to use the senses of hearing, visual or more focused by using the senses of sight and kinesthetic which are more likely to use the senses of taste so that the teacher must be able to create learning styles that suit the needs of students. The aim of this research is to develop an effective, practical, and valid Blended Learning-based mathematics learning tool in terms of students' learning styles. This study uses the Research and Development method. R & D research is writing that describes the development of a learning device product in stages. The results of the research show that the level of validity of developing mathematics learning tools based on Blended Learning in terms of the learning styles of students is said to be valid because they obtained scores of 0.75 and 0.8, the percentage of effectiveness was 73% for small-scale trials and 77% for large-scale trials, and the level of practicality of device development learning mathematics based on Blended Learning in terms of the learning styles of students is very practical based on the positive responses from the interview results.